Deletion of Lys 107 modify the ability of apoA-I to self-associate in solution. - Díaz Ludovico, Ivo (2020)
Human apolipoprotein (apo)A-I is the primarily protein component of high-density lipoproteins (HDL) where it plays a pivotal role in governing HDL metabolism. The deletion mutant Lys107del (∆K107) is a natural variant of apoA-I which is associated with hypertriglyceridemia and accelerated atherosclerosis in carriers. While the impact of ∆K107 on HDL metabolism and cardiovascular disease has been extensively studied, little information exists on the structural mechanisms resulting in the observed phenotypes. The purpose of this study was to investigate and identify the structural differences between wild-type (Wt) and ∆K107 apoA-I driving the dysfunctional lipoprotein metabolism observed in the carriers. Chemical cross-linking was used to capture monomeric, dimeric, trimeric, and tetrameric Wt and ∆K107 apoA-I. SDS-PAGE showed a shift in distribution of the oligomeric species with ∆K107 existing primarily as a monomer compared to Wt apoA-I. Respective species were isolated by size exclusion chromatography which confirmed the observed differences in the distribution of the oligomeric species. No significant differences were observed in fluorescence measurements between oligomers in Wt or ∆K107 apoA-I indicating similar environments for Trp residues. Respective species were subjected to liquid chromatography-mass spectrometry (LC-MS) to determine differences in the cross-linking pattern between the respective oligomers of Wt and ∆K107 apoA-I. Using a combination of SimXL and quantitative cross-linking, we observed a shift in the abundance of cross-links between residues 140-239, 140-118, 226-182, 208-118, 23-59. Our work indicates that ∆K107 preferentially exists as a monomer in solution and cross-linking shows differences in the structural conformation of ∆K107 compared to Wt apoA-I. These observed structural changes may contribute to the observed phenotypes in carriers of ∆K107 .